Experimental and thermodynamic investigation on isothermal performance of large-scaled liquid piston. (15th June 2022) - Li, Chengchen; Wang, Huanran; He, Xin; Zhang, Yan
Abstract: Hydro-pneumatic Energy Storage (HYPES) is one of the research hotspots by introducing liquid piston's isothermal/near-isothermal compressed method to compressed air energy storage. This paper focuses on heat transfer behavior of liquid piston according to experimental result. Firstly, a case is proposed to show the isothermal compressed performance of liquid piston with a 24.71 m 3 cylinder: average temperature rises 10.59 K with a compressed ratio of 1.86. Models have been validated by experimental data. Secondly, heat transfer of compressed process has been investigated. The temperature distribution is uniform and exergy efficiency during compressed process is 86.9%: 85.4% of input exergy transfers into the pressure exergy of air. Additionally, availability analysis has been conducted. Ambient temperature has little influence on isothermal compressed process. Initial pressure affects liquid piston through air mass while pump flow rate affects liquid piston through compressed time. Moreover, cycle performance on practical process considering residual air has been studied with two scaled cases. Starting at ambient condition, both cases keep stable since the second cycle and show a good isothermal performance with large compressed ratio. The highest temperature is at the end of compressing, while the lowest temperature occurs in expanding process. Highlights: An isothermal compressed experiment of large-scaled liquid piston is shown. Heat transfer behavior of each part in a cylinder is investigated. In-depth compressed performance based on the second law of thermodynamic. Analysis of cycle performance based on practical process.